Industrial solid waste: Composite with glass fiber reinforced plastic waste (Research, Society and Development, 2020)
The use of polymeric composites by the industry is due to their lightness and versatility in adapting to complex designs. However, waste generators can be difficult to recycle, which are often placed in landfills, which causes the need for actions that will minimize the amount of this waste generated. Therefore, this work aims to evaluate the mechanical and physical response of the E-glass fiber composite with the polyester matrix, when incorporating waste generated from glass fiber reinforced plastic (GFRP). For this purpose, three plates were hand lay-up method of manufacturing, all produced in E-glass / polyester, however, in two of them, 10% and 15% of the GFRP residues were incorporated by weight of resin. The test of density, moiture, mechanical uniaxial tensile and bending in three points were performed based on the standards ASTM D792, ASTM D5259, ASTM D3039 and ASTM D790, respectively, seeking to characterize and evaluate the mechanical response after inserting the waste in the composite. The results showed that the samples with residue absorbed more moisture and became lighter. However, there was a loss of mechanical strength, both in traction and flexion, for the two compositions with added residues, compared to samples of the composite without residue. However, the fracture characteristic was similar for the three composites evaluated. It is noteworthy that losses in properties do not prevent the use of residues in these composites, once the mechanical demands and the service conditions in which they will be exposed are known.